Jan Čep’s fascinations and inspirations of Karel Hynek Mácha - Seidel-Mączyńska, Aleksandra (Poznańskie Studia Slawistyczne, 2011)
Among various Čep’s literary fascinations, Karel Hynek Mácha retains an important place. The Romantic writer (Mácha) and the 20th century Catholic novelist (Čep) are connected mainly by the same conception of a man in his relationship with the world and God. They share the same approach towards the passing of time, which in turn seems to be the key to being and understanding existence. The fascination dedicated to Mácha’s writing seems to conceal the vision of poets and source of creation shared by both the authors. Art and artists take on a specific role, which results from the particular spiritual predispositions of the author and from his metaphysical anxiety, which has its roots in the perception of mystery surrounding humankind and the world.